Return to work after acromioclavicular joint stabilization: a retrospective case control study - Porschke, Felix; Schnetzke, Marc; Studier-Fischer, Stefan; Grützner, Paul Alfred; Gühring, Thorsten (Journal of orthopaedic surgery and research, 2019)
Considering the epidemiology of acromioclavicular (AC) dislocation related to young and active patients, the impact on working capacity is highly relevant. The purpose of this study was to determine the capacity of work and time to return to work (RTW) after AC joint stabilization. We hypothesized that manual working patients show more restrictions returning to work.